Cancer cachexia impairs neural respiratory drive in hypoxia but not hypercapnia. Issue 1 (25th October 2018) - Fields, Daryl P.; Roberts, Brandon M.; Simon, Alec K.; Judge, Andrew R.; Fuller, David D.; Mitchell, Gordon S.
Abstract: Background: Cancer cachexia is an insidious process characterized by muscle atrophy with associated motor deficits, including diaphragm weakness and respiratory insufficiency. Although neuropathology contributes to muscle wasting and motor deficits in many clinical disorders, neural involvement in cachexia‐linked respiratory insufficiency has not been explored. Methods: We first used whole‐body plethysmography to assess ventilatory responses to hypoxic and hypercapnic chemoreflex activation in mice inoculated with the C26 colon adenocarcinoma cell line. Mice were exposed to a sequence of inspired gas mixtures consisting of (i) air, (ii) hypoxia (11% O2 ) with normocapnia, (iii) hypercapnia (7% CO2 ) with normoxia, and (iv) combined hypercapnia with hypoxia (i.e. maximal chemoreflex response). We also tested the respiratory neural network directly by recording inspiratory burst output from ligated phrenic nerves, thereby bypassing influences from changes in diaphragm muscle strength, respiratory mechanics, or compensation through recruitment of accessory motor pools. Results: Cachectic mice demonstrated a significant attenuation of the hypoxic tidal volume (0.26mL±0.01mL vs 0.30mL±0.01mL; p<0.05), breathing frequency (317±10bpm vs 344±6bpm; p<0.05) and phrenic nerve (29.5±2.6% vs 78.8±11.8%; p<0.05) responses. On the other hand, the much larger hypercapnic tidal volume (0.46±0.01mL vs 0.46±0.01mL; p>0.05), breathing frequency (392±5bpm vs 408±5bpm; p>0.05) and phrenic nerve (93.1±8.8% vs 111.1±13.2%; p>0.05) responses were not affected. Further, the concurrent hypercapnia/hypoxia tidal volume (0.45±0.01mL vs 0.45±0.01mL; p>0.05), breathing frequency (395±7bpm vs 400±3bpm; p>0.05), and phrenic nerve (106.8±7.1% vs 147.5±38.8%; p>0.05) responses were not different between C26 cachectic and control mice. Conclusions: Breathing deficits associated with cancer cachexia are specific to the hypoxic ventilatory response and, thus, reflect disruptions in the hypoxic chemoafferent neural network. Diagnostic techniques that detect decompensation and therapeutic approaches that support the failing hypoxic respiratory response may benefit patients at risk for cancer cachectic‐associated respiratory failure.